The potential effects of Ocimum basilicum on health: a review of pharmacological and toxicological studies. (3rd July 2018) - Sestili, Piero; Ismail, Tariq; Calcabrini, Cinzia; Guescini, Michele; Catanzaro, Elena; Turrini, Eleonora; Layla, Anam; Akhtar, Saeed; Fimognari, Carmela
ABSTRACT: Introduction : Basil ( Ocimum basilicum L ., OB) is a plant world widely used as a spice and a typical ingredient of the healthy Mediterranean diet. In traditional medicine, OB is indicated for many maladies and conditions; OB-containing nutritional supplements are increasingly sold. Conversely, safety concerns have been raised about the promutagens and procarcinogens alkenylbenzenes contained in OB. Areas covered : A critical review of the current status of OB as a nutraceutical, the pharmacology of its bioactive components, the rationale for its indications, and its safety. Expert opinion : Due to the polyphenolic and flavonoidic content, OB can be considered as an important ingredient in healthy diets; OB preparations may be effective as chemopreventive agents or adjunctive therapy in the treatment of different clinical conditions. From a toxicological perspective, since the tumorigenic potential of alkenylbenzenes is counteracted by other OB constituents such as nevadensin, it can be concluded that OB consumption in food and preparations is safe. The only concern relates to OB essential oils: in this case, a concentration limit for alkenylbenzenes should be precautionary defined, and the use of plant chemotypes with no or low levels of these alkylbenzenes for the preparation of essential oils should be made compulsory.